2022
DOI: 10.3389/fonc.2022.929838
|View full text |Cite
|
Sign up to set email alerts
|

ACO1 and IREB2 downregulation confer poor prognosis and correlate with autophagy-related ferroptosis and immune infiltration in KIRC

Abstract: BackgroundACO1 and IREB2 are two homologous cytosolic regulatory proteins, which sense iron levels and change iron metabolism–linked molecules. These two genes were noticeably decreased in kidney renal clear cell carcinoma (KIRC), which confer poor survival. Meanwhile, there is a paucity of information about the mechanisms and clinical significance of ACO1 and IREB2 downregulation in renal cancers.MethodsThe expression profiles of ACO1 and IREB2 were assessed using multiple public data sets via several bioinfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 58 publications
(80 reference statements)
0
10
0
Order By: Relevance
“…Frontiers in Pharmacology frontiersin.org light chain after inhibition, leading to a decreased intracellular free iron level and inhibiting the emergence of ferroptosis (Zhu et al, 2022).…”
Section: Intracellular Fe 2+ Overloadmentioning
confidence: 99%
“…Frontiers in Pharmacology frontiersin.org light chain after inhibition, leading to a decreased intracellular free iron level and inhibiting the emergence of ferroptosis (Zhu et al, 2022).…”
Section: Intracellular Fe 2+ Overloadmentioning
confidence: 99%
“…The multi-kinase inhibitors sorafenib is recommended to be the first-line strategy for treating advanced ccRCC patients ( 30 , 31 ). Interestingly, it can block the system Xc - function, induce GSH consumption and lipid ROS accumulation, and thus trigger ferroptosis in RCC cells ( 32 34 ). Therefore, comprehensive exploration of the FPTOSs expression profiles could deepen the understanding of occurrence and progression of ccRCC.…”
Section: Discussionmentioning
confidence: 99%
“…These studies are important for deepening our understanding of the basic of cellular life activities, molecular mechanisms of cancer occurrence and development, and drug development. For instance, Zhu et al confirmed that two genes, ACO1 and IREB2, are strong prognostic biomarkers for patients with RCC, and they were associated with RCC autophagy, ferroptosis, and immune infiltration (37).…”
Section: Discussionmentioning
confidence: 99%